Determinación de la discapacidad mental para considerar el aborto no punible señalado en el art. 150 numeral 2 del código orgánico integral penal - Chinachi Sotalin, Natali Cecibel (2017)
The Organic Code of Criminal Integral, in Art. 150 disclaims responsibility and considers not punishable abortion, when it has been practiced by a doctor or other trained health, which has the consent of the woman, her spouse, partner or close relatives, where it has been practiced to prevent danger to life or health of the pregnant mother and if this danger can not be avoided by other means, or if the pregnancy results from a rape or a woman suffering from disabilities mental. In the case that is not punishable abortion by the fact that women suffering from mental disability and pregnancy is a result of rape, disability of mind that is a very general situation in which the type of disability is indicated , this leads to a subjective analysis of the prosecutor and judge to sanction or not abortion under these circumstances, which is necessary to objectively specify the degree of mental disability, because in any case affect the right to inviolability of life guaranteed in Art. 66 paragraph 1 of the Constitution of the Republic of Ecuador, and in Art. 45 of the constitutional provision guarantees that the State recognizes and guarantees life, including the care and protection from conception. Which aims to safeguard the lives of people from the moment they are conceived in the womb, a fact that leads to punish those who violate these rights, rules should be regulated for punishment under criminal law The issue focuses on the adjective field, because the prosecutor will investigate whether the abortion was performed under these circumstances or not, determine whether there was rape, which should prevail complaint, medical expertise and psychological or psychiatric report, then all they complement the procedural historical truth that a crime has occurred against sexual freedom of the abortion victim. And the prosecutor confirm that harmful to dismiss or refrain from accusing event. Regarding mental disability, brings much discussion, since the term mental disability is very wide and leads to qualify wrongly in many women as legal abortion, with the justification of mental disability, performing facts are allowed to voluntary acts are to be punished as crimes. It is necessary that abortion for rape on a woman suffering from mental disability, indicated categories to determine their criminal responsibility, because every woman with disabilities have the card that CONADIS, by so this amplitude creates impunity in this crime. And the prosecutor, make mistakes, without an expertise that will determine the understanding of behavior of the victim against abortion.